Restrictions on Alcohol Sales During Nighttime Hours and Protection Of Health and Safety of Children From Alcoholic Families - A Comparative Legal Perspective - Wilanowska, Monika (Medicine, Law & Society, 2024)
Children growing up in families with alcohol problems often struggle with many problems in the area of physical and mental health, as well as insecurity. One of the priorities for states to conduct anti-alcohol policies should be to ensure them safety. The tool that can be used to reduce the availability of alcohol is to restrict the sales of alcoholic beverages in the area of specific local government units or the country as a whole. The analysis of the regulations of Poland, England, Wales and Lithuania shows that each of them presents a different approach to alcohol policy. All the selected countries have introduced solutions into the legal system that make it possible to limit or prevent the sale of alcoholic beverages at nighttime. Still, the rules for their application are different. Effective application of such solutions in practice can, therefore, lead to a decrease in the amount of alcoholic beverages consumed in the area, which can consequently improve the situation of children in families with alcohol problems.